The Anti-Aggregative Peptide KLVFF Mimics Aβ1-40 in the Modulation of Nicotinic Receptors: Implications for Peptide-Based Therapy - Hanna Trebesova; Guendalina Olivero; Mario Marchi; Massimo Grilli (Biomedicines, 2022)
In recent years, the inhibition of beta-amyloid (Aβ) aggregation has emerged as a potential strategy for Alzheimer’s disease. KLVFF, a small peptide corresponding to the aminoacidic sequence 16-20 of Aβ, reduces Aβ fibrillation dose dependently. Therefore, the toxic and functional characterization of its brain activity is fundamental for clarifying its potential therapeutic role. Accordingly, we studied the modulatory role of KLVFF on the cholinergic receptors regulating dopamine and noradrenaline release in rat synaptosomes. Nicotinic receptors on dopaminergic nerve terminals in the nucleus acccumbens are inhibited by KLVFF, which closely resembles full-length Aβ1-40. Moreover, KLVFF entrapped in synaptosomes does not modify the nicotinic receptor’s function, suggesting that external binding to the receptor is required for its activity. The cholinergic agent desformylflustrabromine counteracts the KLVFF effect. Remarkably, muscarinic receptors on dopaminergic terminals and nicotinic receptors regulating noradrenaline release in the hippocampus are completely insensitive to KLVFF. Based on our findings, KLVFF mimics Aβ1-40 as a negative modulator of specific nicotinic receptor subtypes affecting dopamine transmission in the rat brain. Therefore, new pharmacological strategies using the anti-aggregative properties of KLVFF need to be evaluated for potential interference with nicotinic receptor-mediated transmission.